Infection and Pediatric Acute Lymphoblastic Leukemia - Ma, Xiaomei (2008)
In this review, we provide an overview of recent findings from the Northern California Childhood Leukemia Study (NCCLS) on factors related to the immune system including child's vaccination history and measures of child's exposure to infectious agents, namely daycare attendance, infection during infancy, and parental social contact in the work place. We also provide suggestions for the next stages of studies.